Numerical and Experimental Study on the Indoor Climate in a Classroom with Mixing and Displacement Air Distribution Methods - Weixin Zhao; Panu Mustakallio; Sami Lestinen; Simo Kilpeläinen; Juha Jokisalo; Risto Kosonen (Buildings, 2022)
One main challenge of air distribution in classrooms is to guarantee ventilation performance under different usage conditions. In this study, the indoor climate in summer and winter conditions with different occupancy densities in the classroom is presented. Thermal condition measurements of a half-size classroom were performed in a test room with four air suppliers: wall-grilles, ceiling diffusers, perforated duct diffusers, and displacement ventilation. Those measured data were used for CFD validation of the whole classroom. With CFD simulations, indoor climate parameters with different air diffusers are compared in summer and winter conditions. The results show that displacement ventilation gives the best performance in the occupied zone. The air change efficiency can be reached with displacement ventilation of 1.4 and of only 1 with the other three air diffusers. The air velocities were reasonably low (<0.3 m/s), and the indoor was quite uniform with ceiling diffusers, which is another well-performing solution for classrooms. Corridor wall-grilles give uniform thermal conditions but can have high velocities (0.4 m/s) on the perimeter side of the room space. The air distribution from the perforated duct diffuser is unstable, which causes high local draft (over 20%) in the occupied zone.